Effect of α‐Hederin on IL‐2 and IL‐17 mRNA and miRNA‐133a Levels in Lungs of Ovalbumin‐Sensitized Male Rats. Issue 2 (10th February 2016) - Ebrahimi, Hadi; Fallahi, Maryam; Khamaneh, Amir Mahdi; Ebrahimi Saadatlou, Mohammad Ali; Saadat, Saeideh; Keyhanmanesh, Rana
ABSTRACT: Preclinical Research α‐hederin, a saponin that is a major constituent of English Ivy ( Hedera helix ) is effective in the treatment of asthma. In the present study, the effect of α‐hederin on lung tissue pathology and the levels of the inflammatory mediators; IL‐2 mRNA, IL‐17 mRNA, and MicroRNAs (miRNA)‐133a was evaluated in a rat ovalbumin (OVA)‐sensitized model of asthma. Rats were divided randomly into control (C), OVA‐sensitized (S), OVA‐sensitized pretreated with the antioxidant, thymoquinone (3 mg/kg, S + TQ) or OVA‐sensitized pretreated with α‐hederin (0.02 mg/kg, S + AH) groups. Levels of IL‐2 and IL‐17 mRNA were higher in the OVA‐sensitized group than controls while the level of miRNA‐133a gene expression was lower. IL‐2 mRNA and miRNA‐133a gene expression in the S + TQ group was higher than in the control and OVA‐sensitized groups while the level of IL‐17 mRNA in the S + TQ group was lower than in the OVA‐sensitized group. Pretreatment with α‐hederin decreased IL‐17 mRNA levels and increased miRNA‐133a gene expression compared with OVA‐sensitized animals. All pathological changes in pretreated groups were lower than the OVA‐sensitized group. These results showed a beneficial effect of α‐hederin in OVA‐sensitized rats, suggesting that α‐hederin affects the IL‐2 and IL‐17 secretion pathways, altering miRNA‐133a expression. Drug Dev Res 77:87–93, 2016.   © 2016 Wiley Periodicals, Inc.